Commuter Student at CSU Channel Islands: Transportation, Time, and Engagement - Sexton, Grace; Downey, Dennis (CBR@CSUCI: An annual volume of community-based research, 2019)
This research was conducted to better understand commuter students at CSUCI – focusing on patterns of transportation and time use, and actual and desired campus engagement. The purpose was to collect and report on systematic data that to assist in the development of programs to better serve the needs of commuter students. The project includes two components: a survey conducted in the spring of 2013 and a series of micro-interviews (designed to be 2-3 minutes each) conducted in the spring of 2014. The survey was conducted online, and includes data from 113 respondents. Interviews were designed to cross-check and expand on the survey findings with open-ended responses, and include data from 78 respondents. Findings are presented in the following areas: commuter student demographics; patterns of transportation; time use on and off campus; and interests in campus engagement.